2006
DOI: 10.1111/j.1469-7580.2006.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and failure of cartilage in the tensile mode

Abstract: The aim of this study was to visualize, at the ultrastructural level, the deformation and failure mechanism of cartilage matrix in the tensile mode. Full-thickness dumbbell-shaped specimens were prepared from adult bovines.There were two specimen groups; in the 'parallel' group the specimen axis was parallel to the split lines defining the preferential orientation of the collagen in the articular surface, and in the 'perpendicular' group the specimen axis was perpendicular to the split lines. Specimens were pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…6a), a small area with elevated stress was observed at the defect rim. The absolute values at this area exceeded a suggested cartilage failure limit of 7 MPa1843 during the peak loads of the stance (approximately at 10–30% and 80–90% of the stance). At other time points, the stresses were found to be well below the suggested failure limit.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…6a), a small area with elevated stress was observed at the defect rim. The absolute values at this area exceeded a suggested cartilage failure limit of 7 MPa1843 during the peak loads of the stance (approximately at 10–30% and 80–90% of the stance). At other time points, the stresses were found to be well below the suggested failure limit.…”
Section: Resultsmentioning
confidence: 75%
“…During those time periods, they reached levels that could induce either chondrocyte death46 or failure of collagen crosslinks47. Furthermore, the stress concentrations on the defect rim at peak loads could also imply the initiation of collagen matrix degeneration in the superficial layers of the tissue1843. Exceeding the suggested failure limits of any of these parameters could lead to propagation of the defect and OA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Park et al reported physiological strains of 20% for native cartilage under normal loading conditions [40]. Failure strain and stress of cartilage in tension tested at 1%/s strain rate was reported between 25% and 30% and approximately 3-5 MPa, respectively [41]. Kaukinen et al reported destructive compressive stress and strain values for cartilage-bone plugs of 4.6 ± 2.0 MPa and 50 ± 6% when tested at 3.5%/s strain rate [42].…”
Section: Discussionmentioning
confidence: 95%
“…The maximum strain (26%) and reference strain (14.3%) were, however, both below the reported critical strain. 9,23,35 The supraspinatus was the most sensitive muscle to the 2 anatomic parameters. As expected, GI had a smaller effect on supraspinatus forces than AI and consequently on glenohumeral joint forces.…”
Section: Discussionmentioning
confidence: 99%